1993
DOI: 10.1111/j.1468-2257.1993.tb00959.x
|View full text |Cite
|
Sign up to set email alerts
|

Migration Regions and Interstate Labor Flows by Occupation in the United States

Abstract: "This paper investigates the migration patterns of occupational groups [in the United States]. The results confirm previous analyses of the differences in movement behavior between occupations but, in addition, show that this variation is a function of the industrial sector of employment. The chief aim of the paper, however, is to uncover the geography of labor flows for different occupational groups using a principal components analysis of interstate flow matrices....Results indicate that migration regions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 38 publications
(60 reference statements)
0
14
0
Order By: Relevance
“…Many studies have shown a relationship between migration propensity and employment and occupational factors (Ellis et al 1993;Greenwood 1985;Herzog et al 1993;Warnes 1983). Traditional models of migration relate it to workers' desires to find employment and to maximise wages.…”
Section: Confounding Factors In the Relationship Between Migration Anmentioning
confidence: 98%
“…Many studies have shown a relationship between migration propensity and employment and occupational factors (Ellis et al 1993;Greenwood 1985;Herzog et al 1993;Warnes 1983). Traditional models of migration relate it to workers' desires to find employment and to maximise wages.…”
Section: Confounding Factors In the Relationship Between Migration Anmentioning
confidence: 98%
“…The most relevant research to our work was by Long Long (1973) who found that differences in occupational flows can largely be described by demographic features and the educational attainment of the members of a given occupation group. More recently Ellis et al (1993) examine the 1980 data focusing on the geographic structure of occupational migration flows and found evidence of distinct subsystems of interstate migration flows differentiated by occupation. The former research would seem to indicate that efforts to integrate migration into occupational employment projections would not be justified whereas the latter results on occupational subsystems would support the effort.…”
Section: Characteristics Of Occupational Migrationmentioning
confidence: 99%
“…Long distance migration from locations that sharply contrast with the Weser-Ems region in terms of culture, topography and landscape, dialect or language was undertaken mainly by managers for top-level positions; another endorsement for the general hypotheses of a correlation between career-achievement and spatial mobility (Ellis et al, 1993;Owen & Green, 1992). The in-migrants came from all over Germany.…”
Section: Recruitment Strategies 57mentioning
confidence: 99%